Selected synthetic strategies to cyclophanes - Kotha, Sambasivarao; Shirbhate, Mukesh Eknath; Waghule, Gopalkrushna T. (Beilstein Journal of Organic Chemistry, 2015)
In this review we cover various approaches to meta- and paracyclophanes involving popular reactions. Generally, we have included a strategy where the reaction was used for assembling the cyclophane skeleton for further functionalization. In several instances, after the cyclophane is made several popular reactions are used and these are not covered here. We included various natural products related to cyclophanes. To keep the length of the review at a manageable level the literature related to orthocyclophanes was not included.
Keywords: addition reactions; coupling reactions; cyclophane; metathesis; muscopyridine; name reactions; natural products